Penetrating neck injury with consequential thoracic complications managed with use of video-assisted thoracoscopic surgery – A case report - Vešović, Nataša; Ristanović, Aleksandar; Cvijanović, Vlado; Stojković, Dejan; Marić, Nebojša; Kostovski, Vanja; Djenić, Ljubinko; Nikolić, Aleksandar (Vojnosanitetski pregled, 2021)
Introduction. Penetrating injuries of the neck are potentially life-threatening conditions. They can cause injuries of larynx, trachea, esophagus and major blood vessels in this area. Case report. The patient was a 28-year-old male who was stabbed with broken glass penetrating the front side of the base of his neck. The patient had dyspnea and the wound was inflicted the night before admission to hospital. An otorhinolaryngologist found a stab wound in the region of the left basis of the neck. The wound was 2 cm long with no signs of bleeding and deep injuries of the anatomical structures of the neck. However, since left hemopneumothorax was clinically and radiologically apparent, drainage of the thorax was performed upon admission to the intensive care unit. Initially, 400 mL of hemorrhagic effusion was evacuated. However, 24 hours later the patient became hemodynamically unstable. It was an indication for video-assisted thoracoscopy (VATS). Therefore, VATS was used as a diagnostic method in order to determine the nature of the injury. Intraoperatively, we treated a laceration of pleuropulmonary adhesion which was continuously bleeding from the apex of the thoracic cavity. As a result, adequate surgical hemostasis was achieved. Furthermore, during the three-week postoperative period, thoracic tubes were placed due to the prolonged air leakage. A thoracic tube was placed laterally along with another one which was placed in intercostal space higher. After total reexpansion of the left lung, thoracic tubes were extracted, and the patient was discharged. Conclusion. Nowadays, VATS has become a highly important ultimate treatment of thoracic trauma. This minimally invasive method allows us to verify injury type and localization, to resolve it and further to follow-up evaluation of pathological changes in the lungs, pericardium, mediastinum, pleura and thoracic wall. In the case of stab wounds in the cervical region, any injuries of the lungs and pleura must be taken into consideration.
Keywords: neck injuries; hemothorax; pneumothorax; drainage; thoracoscopy; minimally invasive surgical procedures